Does fund management level of risk affect the fund performance? - Mahat, Fauziah; Ali, Noor Azman; Md Nassir, Annuar (World Business Institute, 2011)
Fund management risk tolerance is a topic which is of enormous interest not only to many researchers but also to investors. Motivated by limited empirical studies on the effects of risk tolerance on fund performance in Malaysia and in response to reasonable gaps in the literature, the objective of this paper is to examine the moderating effects of fund risk tolerance on the fund characteristics and fund performance relationship. The fund characteristics consist of the type of fund, fund categories, investment objectives, and popularity of fund. Meanwhile, the time horizon and risk profile are the proxies to measure the level of risk for the fund. The fund performance measures in this study use Sharpe ratio as the fund performance measurement. The findings revealed that time horizon acts as a moderator variable on the relationship between type of fund, popularity fo fund and fund performance measured by Sharpe ratio, but does not moderate on the relationship between categories of fund, investment objective and fund performance. In addition, when risk profile was included in the test, the results indicate that the relationship of type of fund and popularity of fund with fund performance measured by Sharpe ratio is significantly moderated by the firm risk profile).